Hopeful, Harmless, and Heroic: Figuring the Girl Activist as Global Savior. Issue 2 (1st June 2020) - Taft, Jessica K.
Abstract: There has been a notable increase in the public visibility of girl activists in the past ten years. In this article, I analyze media narratives about several individual girl activists to highlight key components of the newly desirable figure of the girl activist. After tracing the expansion of girl power discourses from an emphasis on individual empowerment to the invocation of girls as global saviors, I argue that girls are particularly desirable figures for public consumption because the encoding of girls as symbols of hope helps to resolve public anxieties about the future, while their more radical political views are managed through girlhood's association with harmlessness. Ultimately, the figure of the hopeful and harmless girl activist hero is simultaneously inspirational and demobilizing.